PERLINDUNGAN HUKUM HAK-HAK MASYARAKAT HUKUM ADAT TERHADAP DAMPAK NEGATIF ILLEGAL LOGGING - Hariyadi, Wicaksono Putra (Solusi, 2019)
Forest damage due to illegal logging and logging is known as illegal logging. Legal protection of the rights of indigenous and tribal peoples to the negative impacts of illegal logging based on the concept of national law and customary law can be done by protecting the interests of indigenous peoples, particularly through legislation, namely Article 67 Article (1) (2) and (3) of the Law Law No. 41 of 1999 concerning Forestry. The need for legal protection for indigenous peoples is vulnerable to violations or neglect of their human rights. The state has the responsibility to promote, protect and uphold human rights against its citizens.